Characterization of the dry stone heritage of the Barrocal region (Algarve, Portugal) - Balsells, Cèlia Mallafrè (2022)
The paper aims to value the diverse and important dry stone heritage located in the Barrocal area (Algarve, Portugal). The dry stone construction technique and the set of constructions that derive from its application are present in all parts of the world where stone is present. Throughout the Iberian Peninsula and specifically in the territory of Portugal, there are different dry stone constructions that make up the rural landscape. They are an example of the work in the field and the use of local natural resources during different generations. The recognition by UNESCO as Intangible Cultural Heritage of Humanity (2018) highlights the importance of maintaining a construction technique that, transmitted orally, is materialized in different constructions according to the constructive heritage and the stone typology of the nearby environment. The study focuses on a specific partially cultivated area of the Barrocal where different types of construction of dry stone elements exist. Starting from the contextualization of the studies carried out throughout Portugal, the predominant dry stone constructions of the Barrocal, the area with the greatest presence of a variety of types of the Algarve, are being identified, recorded and analysed. The work provides a classification of the present constructions in the area linked to their use and provides data on the construction characteristics and the typology of the stone. The knowledge of these constructions makes it possible to explain the economic and social context of a certain period and to plan reactivation measures for other economic sectors not linked to tourism. The Algarve, one of the most touristic areas of Portugal, has focused most of its economy on beach tourism, leaving the cultural and dry stone architectural heritage almost unnoticed.The constructions and the dry stone construction technique are a way of preserving the rural landscape and the cultural memory so that the benefits related to ecology and biodiversity are observed through this document.